PREFERENSI WISATAWAN MILENIAL MANCANEGARA KE BADUNG, BALI - Mia Ayu Saputri, Ni Kadek; Kusuma Negara, I Made; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020)DO - 10.24843/IPTA.2020.v08.i01.p05, 2020)
In this era of tourism activities become a trend for the millennial generation. In tourism activities, of course, there are considerations in choosing an object as a destination for a tour or referred to as a reference. Tourist preferences need to be known to measure how much tourist interest in a tourist attraction. Badung, Bali is one of the biggest destinations for foreign tourists. The purpose of this study was to determine the characteristics, preferences, and attitudes of milenial tourists in choosing a tourist attraction in Badung. Data analysis techniqes used in this study is observation, questionnaire. Quantitative descriptive data analysis technique with the calculation of cross-tabulation and chi-square analysis and ideal point models. A total of 120 respondents were selected purposively, namely milenial foreign tourists aged 18 - - 37 years. The characteristics of milenial tourists in this study the majority are aged 25 - - 30 years, Country of origin Australia, last high school education, unmarried status, aiming for a vacation, staying 4 - - 7 days, first visit, traveling with friends. The preferences of milenial tourists there are 9 preferences, among others, tourist activities where tourists choose to look around, on milenial tourists choose villas, where to eat millennial tourists choose restaurants, and on transportation, millennial tourists choose family cars. On Sosial Media used by tourists choosing Instagram, when using Sosial Media tourists choose 4 - - 6 hours, when uploading photos of millennial tourists choose a few hours after editing photos, on information sites used by millennial tourists choose Google, and on photo capture tools that are used by millennial travelers to choose mobile phones. The attitude of millennial tourists in this study is that Badung has a tourist attraction that can be interpreted as good millennial tourist attitudes.